Sinus floor augmentation using mixture of mineralized cortical bone and cancellous bone allografts: Radiographic and histomorphometric evaluation - Hyun-Woo Kim (Journal of Dental Sciences, 2020)
Background/purpose: Due to the pneumatization of the maxillary sinus, the sinus floor augmentation is often performed to implant placement in the maxillary posterior region. The aim was to perform radiographic and histomorphometric evaluation after placement of mixed allografts (cortical freeze-dried bone allograft [FDBA] 50%:cancellous FDBA 50%) during sinus floor augmentation. Materials and methods: In 37 patients, anorganic bovine bone (ABB, sites = 16), mineralized cancellous bone allograft (MCBA, sites = 15), and mixed allografts (Mixed AG, sites = 20) were placed during sinus floor elevation via the lateral approach (LSFE), at total 51 sites with residual alveolar bone height (RBH) < 5 mm. Cone-beam computed tomography images were obtained before LSFE (T0), after surgery (T1), and 6 months after surgery (T2) for radiographic analysis. After a 6-month healing period, core biopsies were harvested and histomorphometric analysis was performed. Results: The mean augmented bone height (ABH) of ABB, MCBA, and mixed AG groups after surgery was similar (13.86 ± 4.19 mm, 13.99 ± 4.07 mm, and 14.20 ± 3.12 mm, respectively; P > 0.05). The mean ABH of ABB, MCBA, and mixed AG groups after 6 months was similar (13.72 ± 4.55 mm, 11.83 ± 3.31 mm, and 12.53 ± 2.97 mm, respectively; P > 0.05). In the ABB, MCBA, and mixed AG groups, the proportion of newly formed bone (NB) was similar (36.13 ± 10.01%, 39.26 ± 10.72%, and 31.27 ± 18.31%, respectively; P > 0.05). Conclusion: This result demonstrated that mixed AG led to sufficient bone augmentation and histologically comparable NB formation as compared to ABB and MCBA for sinus floor augmentation.